Perceived Psychotherapist's Empathy and Therapy Motivation as Determinants of Long-Term Therapy Success—Results of a Cohort Study of Short Term Psychodynamic Inpatient Psychotherapy - Vitinius, Frank; Tieden, Stephanie; Hellmich, Martin; Pfaff, Holger; Albus, Christian; Ommen, Oliver (Frontiers in Psychiatry, 2018)
Objective: Outcome predictors and determinants for treatment outcome of inpatient psychotherapy will be assessed in a follow-up-study. Sociodemographic factors and the level of depressiveness at admission, the perceived physician’s empathy rated by patients and the therapy motivation as possible moderators of treatment outcome (reduction of depressive symptoms) are analyzed. Methods: In a cohort study, the outcome of inpatient multimodal psychotherapy was examined with Beck-Depression-Inventory (BDI) at admission (T1), discharge (T2) and at follow-up (1 to 3 years after treatment) (T3). Inclusion criteria were: Inpatient psychotherapy between 2007 and 2010 with a duration of at least one week and complete data set. The influence on therapy success of 1) sociodemographic factors, 2) the perceived physician’s empathy rated by patients using the Consultation and Relational Empathy Measure (CARE) and 3) the therapy motivation of the patients are examined by means of correlation analysis, distribution comparisons and subsequently logistic regression. Results: Ninety-two (64 females, average age 39 yrs.) of 182 eligible patients participated in the follow-up survey. The perceived physician's empathy, therapy motivation, education level and depression at baseline had a significant impact on therapy success. Gender, age and partnership were not significant. The length between discharge and follow-up had no influence on the results. Based on these variables a multiple logistic regression explained 42% of the variation (goodness-of-fit). Conclusion: Due to the shown relevance of the physician's empathy perceived by patients and the therapy motivation of patients for therapy success, both factors should be considered already at the beginning of the therapy. Consequently, they should be recognized in the context of postgraduate training and education.